3D to 2D surface mesh parameterisation for the purposes of unstructured transmission line modelling method simulations - Nasser, Hayan (2016)
Small scale fabrication processes have led to the advent of very thin flexible devices such as RFID tags, flexible PCBs and smart clothing. In a geometrical sense, these present themselves as curved two dimensional surfaces embedded in a three dimensional domain. When simulating electromagnetic behaviour on these surfaces at low frequencies, a full 3D field model is not always necessary. Using 3D algorithms to solve these problems can result in a large portion of the computer memory and runtime being used to mesh and simulate areas of the domain that present little electromagnetic activity.